Genome-Wide Analysis of Light-Regulated Alternative Splicing in Artemisia annua L. - Ma, Tingyu; Gao, Han; Zhang, Dong; Sun, Wei; Yin, Qinggang; Wu, Lan; Zhang, Tianyuan; Xu, Zhichao; Wei, Jianhe; Su, Yanyan; Shi, Yuhua; Ding, Dandan; et al. (Frontiers in Plant Science, 2021)
Artemisinin is currently the most effective ingredient in the treatment of malaria, which is thus of great significance to study the genetic regulation of Artemisia annua. Alternative splicing (AS) is a regulatory process that increases the complexity of transcriptome and proteome. The most common mechanism of alternative splicing (AS) in plant is intron retention (IR). However, little is known about whether the IR isoforms produced by light play roles in regulating biosynthetic pathways. In this work we would explore how the level of AS in A. annua responds to light regulation. We obtained a new dataset of AS by analyzing full-length transcripts using both Illumina- and SMRT-based RNA-seq as well as analyzing AS on various tissues. A total of 5854 IR isoforms were identified, with IR accounting for the highest proportion (48.48%), affirming that IR is the most common mechanism of AS. We found that the number of up-regulated IR isoforms (1534/1378, blue and red light, respectively) was more than twice that of down-regulated (636/682) after treatment of blue or red light. In the artemisinin biosynthetic pathway, 10 genes produced 16 differentially expressed IR isoforms. This work demonstrated that the differential expression of IR isoforms induced by light has the potential to regulate sesquiterpenoid biosynthesis. This study also provides high accuracy full-length transcripts, which can be a valuable genetic resource for further research of A. annua, including areas of development, breeding, and biosynthesis of active compounds.